On government centralization and fiscal referendums: a theoretical model and evidence from Switzerland - Lars P. Feld; Jan Schnellenbach; Christoph A. Schaltegger (Philipps-Universität Marburg, Fachbereich Wirtschaftswissenschaften, 2004)
We propose and test a positive model of fiscal federalism in which centralization is less likely to occur in jurisdictions with referendum decisions on policy centralization. Citizens choose centralization of public spending and revenue in order to internalize spillovers if individual preferences in two jurisdictions are sufficiently homogeneous. Under representative democracy, centralization is inefficiently high because representatives can extract political rents by policy centralization. Referendums thus restrict representatives ability for rent extraction. An empirical analysis using a panel of Swiss cantons from 1980 to 1998 supports the hypothesis that centralization is less likely under referendum decision-making.
Keywords: H1; H7; D72; 330; Centralization; Fiscal Federalism; Fiscal Referendums; Finanzföderalismus; Zentralstaat; Öffentlicher Haushalt; Referendum; Public Choice; Theorie; Schweiz